2019
DOI: 10.12659/msm.917344
|View full text |Cite
|
Sign up to set email alerts
|

Strain Elastography-Targeted Biopsy: Does Prostate Volume Affect Prostate Cancer Detection?

Abstract: Background: The present study aimed to assess the correlation between prostate volume and prostate cancer (PCa) detection by strain elastography (SE)-guided targeted biopsy (TB) compared with conventional transrectal ultrasound (TRUS)-guided systematic biopsy (SB). Material/Methods: This retrospective study enrolled 357 patients suspected to have PCa. All patients received TRUS-guided 10-core SB and SE-guided TB. The sensitivity for PCa detected by SE-guided TB was compared with that by TRUS-guided SB, in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The difference in prostate volume makes it unreliable to rely solely on the size of the ROI to determine the ease of PCa detection. 20–22 We have introduced a new indicator ROI-load, and our results showed that ROI-load was a better indicator for PCa and csPCa patient biopsy than ROI-diameter. In addition, the detection rate of targeted biopsy in PCa and csPCa patients with ROI-load > 5% was closer to the total diagnosis rate than that of systematic biopsy.…”
Section: Discussionmentioning
confidence: 87%
“…The difference in prostate volume makes it unreliable to rely solely on the size of the ROI to determine the ease of PCa detection. 20–22 We have introduced a new indicator ROI-load, and our results showed that ROI-load was a better indicator for PCa and csPCa patient biopsy than ROI-diameter. In addition, the detection rate of targeted biopsy in PCa and csPCa patients with ROI-load > 5% was closer to the total diagnosis rate than that of systematic biopsy.…”
Section: Discussionmentioning
confidence: 87%